Portal Vein Recanalization–Transjugular Intrahepatic Portosystemic Shunt (PVR-TIPS) with superior mesenteric vein access and balloon-assisted shunt placement - Cornelia L. A. Dewald; Frank K. Wacker; Benjamin Maasoumy; Jan B. Hinrichs (CVIR Endovascular, 2023)
Abstract Background To report the technique and outcome of ultrasound-guided percutaneous access to the superior mesenteric vein (SMV) for balloon-assisted portal vein recanalization–transjugular intrahepatic portosystemic shunt (PVR-TIPS) in a patient with chronic portal venous and splenic vein occlusion. Case presentation A 51-year-old, non-cirrhotic patient with severe portal hypertension was admitted for PVR-TIPS. Neither splenic nor hepatic access was feasible due to chronic portal and splenic vein occlusion. Percutaneous ultrasound-guided direct puncture of the SMV was performed to obtain access for balloon-assisted PVR-TIPS. The transmesenteric approach in combination with a balloon puncture technique for PVR-TIPS was successful, and no immediate complications were observed post-procedure. The subsequent follow-up exams showed patent TIPS and SMV without signs of intraabdominal hemorrhage. Conclusion Percutaneous ultrasound-guided superior mesenteric vein access for balloon-assisted PVR-TIPS is a feasible option in cases where hepatic or splenic access is not.